Clinical variation in the treatment of trigger finger: An international survey of orthopaedic and plastic surgeons. Issue 9 (September 2022) - Dijksterhuis, A; Gardiner, M.D.; Pinder, R.M.; Debeij, J.; Rodrigues, J.; Howes, R.; Smith, K.; Jain, A.; Coert, J.H.; van der Heijden, E.P.A.; ,; Anandan, Suresh Madhavan; et al.
Abstract: Trigger finger is a common condition affecting the hand. Therapeutic variability surrounds the management of trigger finger, especially in the mild cases. The aim of this study was to survey secondary care surgeons to describe the current management of trigger fingers. The steering group developed a survey for hand surgeons. Following piloting, the survey was distributed to hand surgeons in the United Kingdom and The Netherlands. A total of 713 plastic surgeons and orthopaedic surgeons were invited to participate in the online survey and 440 (62%) surgeons completed the survey. In both mild and moderate cases of trigger finger, steroid injection was the preferred treatment option. Open surgery was the treatment of choice for severe cases. However, there was variation in delivery of care, including type and dosage of steroid, site of injection, interval between injections, maximum number of injections, type of incision and treatment of patients with diabetes or rheumatoid arthritis. This highlights the need for a better evidence base for the treatment of trigger fingers.